# An equilatetal triangle with the lengths of its sides given in term of a and b.

If the lengths are 4acm,3bcm and (a+b+c)cm.

Find a and b and hence find the length of sides of the triangle.

## the sides are equal, so

4a = 3b

4a = a+b+c

c = 3a-b, so

4(3a-b) = 3b

12a-4b = 3b

12a = 7b

subtracting,

8a = 4b

or

4a = 2b

But, 4a = 3b, so

2b = 3b

b=0

You only supplied two equations for three variables, and 0 is not a likely solution.

Check for typos and try again.

## 123%&&&5&&4%4427366&&*--3-%-$&-&--&%**&%

## Try better U can do it

## 4a= 3b

a=3 b=4

4(3)-7=C

C=5

The sides are 12, 12 ,and12

Curled from an internet Nd decided to share pls whosoever dat wrote it pls furgiv me

## The solution is not well explained

## I don't get it

## I do not understand d solution pls explain.

## From the question I think it should be (a+b+3)cm

4a=3b

4a=a+b+3

4a-3b=0

4a-a-b=3

=4a-3b=0_____(1) *3

3a-b=3_______(2) *4

Using elimination mathod

12a-9b=0

12a-4b=12

Minus

=-5b=-12

b=-12/-5

b=12/5

To find a substitute b in equation (1) to 12/5

At the end, (b=12/5 and a=9/5

Thank you.

## To find the values of a and b, we can use the properties of an equilateral triangle. In an equilateral triangle, all sides are equal in length.

Let's start by setting up the equation using the given side lengths:

4a cm = 3b cm = (a + b + c) cm

Since all sides are equal, we can set any two sides equal to each other:

4a cm = 3b cm

Now, let's solve this equation to find the ratio between a and b:

4a = 3b

Divide both sides of the equation by 4:

a = (3/4)b

Now, we can substitute this value of a in terms of b into the third side length:

(a + b + c) cm = (3/4)b + b + c cm

Since all sides are equal, we can set this equal to one of the side lengths, let's say 4a cm:

(3/4)b + b + c cm = 4a cm

Substitute a = (3/4)b into the equation:

(3/4)b + b + c cm = 4((3/4)b) cm

Simplify the equation:

(3/4)b + b + c = 3b

Now, we can solve for c:

(3/4)b + b + c = 3b

Combine like terms:

7/4 b + c = 3b

Subtract 3b from both sides:

7/4 b - 3b + c = 0

Multiply both sides by 4 to eliminate the fraction:

7b - 12b + 4c = 0

Simplify the equation:

-5b + 4c = 0

Now, we have two equations:

a = (3/4)b

-5b + 4c = 0

We can solve these equations simultaneously to find the values of a and b, and then find the length of the sides of the triangle.

Unfortunately, the information provided is not sufficient to determine the specific values of a and b, and hence the length of the sides of the triangle.